2017
DOI: 10.1111/jce.13263
|View full text |Cite
|
Sign up to set email alerts
|

Single‐incision percutaneous pericardial ICD lead placement in a piglet model

Abstract: Percutaneous pericardial placement of an ICD lead using our novel access tool can be safely performed through a 1 cm incision without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The major advantage of this device and approach is the lack of an abdominal generator pocket. In a previous medium‐term infant porcine study evaluating the PeriPath access port for lead placement, abdominal pocket infections were a significant complication . This prototype miniature pacemaker reduces the potential for infection because of its small size and location within the incision itself, eliminating the need for lead tunneling, additional dissection, or a second incision for an abdominal pocket.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major advantage of this device and approach is the lack of an abdominal generator pocket. In a previous medium‐term infant porcine study evaluating the PeriPath access port for lead placement, abdominal pocket infections were a significant complication . This prototype miniature pacemaker reduces the potential for infection because of its small size and location within the incision itself, eliminating the need for lead tunneling, additional dissection, or a second incision for an abdominal pocket.…”
Section: Discussionmentioning
confidence: 99%
“…We have designed a prototype miniature pacemaker (Medtronic PLC, Mounds View, MN, USA) with a short leadlet that can be inserted using a minimally invasive technique . Our approach utilizes a self‐anchoring single‐incision thoracic access port with two crossed working channels called PeriPath (PeriCor LLC, Bethesda, MD, USA) that facilitates pericardial access under direct‐vision videothoracoscopy . We recently reported successful acute implantation of this device in 12 infant piglets, with a median procedure time of less than an hour and capture thresholds similar to generally accepted values for surgically implanted epicardial pacing leads .…”
Section: Introductionmentioning
confidence: 99%
“…19 Similarly, Clark et al demonstrated feasibility of implanting a defibrillator lead with a “side biting” tine through a pericardial sheath. 20,21 An additional approach towards extravascular pacing demonstrated successful ventricular capture using a substernal electrode. 22 While all of these approaches targeted extravascular lead placements, our system is the first to implant the entire pacing system (pulse generator, lead and electrode) in the epicardial space.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has been described extensively in our previous work. [13][14][15][16] The experimental group (or adhesion group) underwent left thoracotomy and partial pericardiectomy followed by a 6 week recovery period to develop intrathoracic adhesions. Other studies have used similar animal models to develop adhesions by performing a partial pericardiectomy and epicardial irrigation to simulate congenital heart surgery.…”
Section: Methodsmentioning
confidence: 99%
“…13 We demonstrated the feasibility of this approach to implant both ICD leads as well as a prototype miniature pacemaker in an infant porcine model. 13,14 However, these studies were done in animals who had not previously undergone cardiac surgery, and therefore could not be fairly extrapolated to postoperative patients with CHD. The objective of this study was to demonstrate the feasibility of our minimally invasive approach in an infant porcine adhesion model to apply this technique to the population of patients with previous CHD surgery.…”
Section: Introductionmentioning
confidence: 95%